2015
DOI: 10.7595/management.fon.2015.0017
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Growth Rate: Evidence from Agricultural and Food Enterprises

Abstract: Sustainable growth rate is a maximum growth rate that one enterprise may achieve with a given set of financial policies. The growth of an enterprise per rate higher than sustainable growth rate may lead to financial troubles, insolvency, even to the enterprise bankruptcy. In order to be able to finance a rapid growth, the enterprise will have to issue new shares, increase indebtedness, change its dividend policy, increase production efficiency or improve the asset turnover ratio. The enterprise growth per rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Sustainable growth indicates annual sales growth that is consistent with firms' financing policy (Higgins 1977). Based on firms' financing policy, managers will be able to determine the maximum sales level of their firms (Momčilović et al 2015) that will not negatively affect their cash flows (Ashta 2008). Firms' financing policy is related to their decisions not to issue new shares and maintain their debt to equity (DER) ratio at certain levels.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Sustainable growth indicates annual sales growth that is consistent with firms' financing policy (Higgins 1977). Based on firms' financing policy, managers will be able to determine the maximum sales level of their firms (Momčilović et al 2015) that will not negatively affect their cash flows (Ashta 2008). Firms' financing policy is related to their decisions not to issue new shares and maintain their debt to equity (DER) ratio at certain levels.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…It seems that the Serbian government has recognized the importance of food and agricultural sectors for the development of the whole country. However, even though above mentioned data could lead to a conclusion that Serbia has comparative advantages in the field of food sector, Momčilović et al (2015) indicated that suitable circumstances for the sustainable growth were limited or there was no real sustainable growth in this sectors during the previous period. , Year 67, No.…”
Section: Methodsmentioning
confidence: 96%
“…Furthermore, the sector of activity that the company operates in also has a significant impact on the SGR [24][25][26][27][28][29], and so does the company size [7], and these characteristics require adapted operational organization strategies.…”
Section: Corporate Sustainability Growth and Investment Performancementioning
confidence: 99%